Krótka historia budowy Pałacu Kultury i Nauki w Warszawie — fakty znane i nieznane - Burchacki, Łukasz (Wieki Stare i Nowe, 2019)
The article is devoted to the stages of the construction of the Pałac Kultury i Nauki in Warsaw — from the proposal of the construction to the handing over of the building by the Soviet authorities to the Polish party. On the basis of research the author established that the deputy prime minister of the U.S.S.R., Vyacheslav Mikhaylovich Molotov, suggested the construction of the palace on 22 July 1951 instead of 3 July, according to some research works. Then the author describes the circumstances of the creation of the plans of the construction of the high -rise as well as the signing of agreements concerning the initiation of the endeavour to erect the PKiN which was a logistic challenge. Owing to a search query in the archives the author attempted to present the realities of the collaboration between Polish and Soviet labourers which had little to do with the ones presented by the propaganda of that time. For example, on the basis of declassified documents the author managed to provide the number of Poles who lost their lives during the construction of the PKiN.